2019
DOI: 10.3390/nu11081846
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Water Scarcity: Evidence from a Large Australian Population Health Survey

Abstract: There is widespread interest in dietary strategies that lower environmental impacts. However, various forms of malnutrition are also widely prevalent. In a first study of its kind, we quantify the water-scarcity footprint and diet quality score of a large (>9000) population of self-selected adult daily diets. Here, we show that excessive consumption of discretionary foods—i.e., energy-dense and nutrient-poor foods high in saturated fat, added sugars and salt, and alcohol—contributes up to 36% of the water-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 48 publications
5
47
2
Order By: Relevance
“…In a recent study about core and discretionary foods consumed daily by a large (>9000) population of self-selected adults, a potential association between a healthier diet and lower environmental impacts was emphasized [42]. Indeed, this study concluded that "excessive consumption of discretionary foods-i.e., energy-dense and nutrient-poor foods high in saturated fat, added sugars and salt, and alcohol-contributes up to 36% of the water-scarcity impacts and is the primary factor differentiating healthier diets with lower water-scarcity footprint from poorer quality diets with higher water-scarcity footprint" [42]. The authors added that very large reductions in the dietary water-scarcity footprint are therefore possible, notably through technological change, product reformulation, and procurement strategies in the agricultural and food industries.…”
Section: Discretionary Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study about core and discretionary foods consumed daily by a large (>9000) population of self-selected adults, a potential association between a healthier diet and lower environmental impacts was emphasized [42]. Indeed, this study concluded that "excessive consumption of discretionary foods-i.e., energy-dense and nutrient-poor foods high in saturated fat, added sugars and salt, and alcohol-contributes up to 36% of the water-scarcity impacts and is the primary factor differentiating healthier diets with lower water-scarcity footprint from poorer quality diets with higher water-scarcity footprint" [42]. The authors added that very large reductions in the dietary water-scarcity footprint are therefore possible, notably through technological change, product reformulation, and procurement strategies in the agricultural and food industries.…”
Section: Discretionary Foodsmentioning
confidence: 99%
“…On that basis and extended to an ethical and sustainable diet, three golden rules for designing a protective diet food system sustainability have been elaborated in our laboratory, and taking into consideration the neglected dimension of the degree of processing (second rule). In French, this new concept is called the 3Vs Rule for Végétal (animal calories not exceeding 15% per day), Vrai (real: ultra-processed calories not exceeding 15% per day), and Varié (varied real foods), using, if possible, local, seasonal, and organic products [42,133]. In line with previous collective experience searching for a generic complex diet protecting both human health and the planet as a whole with a time horizon of 2050 [7,31,32,[134][135][136][137][138][139][140], the 3Vs concept is based on a holistic view in that, through its application, it protects humans, animals, and the environment as a whole.…”
Section: The 3v's Rule Proposal To Counteract Excess Upf Consumptionmentioning
confidence: 99%
“…To enable integration of the dietary intake data and cropland footprint data, processed foods and mixed dishes were disaggregated into basic components as described previously [49], applying archetypal recipe files published by the ABS [36]. Conversion factors, obtained predominantly from a reference database managed by Food Standards Australia and New Zealand [50], were used to translate cooked food portions into raw quantities.…”
Section: Dietary Intake Datamentioning
confidence: 99%
“…For each of the 9341 adult daily diets, a diet quality score was determined by application of the food-based Dietary Guideline Index (DGI) [57], as described previously [49]. The DGI provides a score out of 100 that reflects overall compliance with the Australian Dietary Guidelines [53].…”
Section: Dietary Quality Analysismentioning
confidence: 99%
See 1 more Smart Citation